PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DAERAH PROVINSI SULAWESI SELATAN - Sulfiani, Sulfiani; Ali, Firman; Faisal, Andi; Irwan, Andi (JURNAL LENTERA BISNIS, 2026)
This study aims to determine the influence of leadership style, organizational culture, and work motivation on the performance of civil servants at the Regional Secretariat of South Sulawesi Province. This study used a quantitative approach, with a sample of 116 non-echelon employees using a census technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the simultaneous test (F test) indicated that leadership style, organizational culture, and motivation jointly had a positive and significant effect on employee performance, with an F-value of 93.841 and a significance level of 0.000 < 0.05. The results of the partial test (t-test) show that leadership style has no significant effect (t = 0.328; sig. 0.744 > 0.05), while organizational culture (t = 5.575; sig. 0.000 < 0.05; β = 0.397) and motivation (t = 6.631; sig. 0.000 < 0.05; β = 0.506) have a positive and significant effect on employee performance. The standardized coefficients (Beta) value shows that the motivation variable has the most dominant influence on employee performance with a Beta value of 0.506, followed by organizational culture of 0.397, while leadership style is 0.022 and is not significant. These results indicate that local government agencies need to prioritize increasing work motivation and strengthening organizational culture in order to improve employee performance sustainably. Although leadership style does not have a significant partial effect, it still contributes simultaneously, thus requiring an adaptive and synergistic leadership style to support the creation of a conducive work environment.